PENETAPAN RASIO BAGI HASIL AKAD MUDHARABAH DAN MUSYARAKAH (STUDI KASUS DI BNI SYARIAH) - Tenny Badina (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2011)
This study is a descriptive case study analysis in PT. Bank BNI Syariah using primary data and secondary data. This study rejects the results of research Mawardi (2005) and Vustany (2006) which states that the granting of a return to the Islamic banking results are influenced by interest rates. The interest rate is only a reference in determining the level of expected return for the customer to determine the ratio of the results. Calculation of profit sharing between users and customers BNI Syariah funds made by the actual return earned business profits, and distribution of the proceeds among the owners BNI Syariah customer funds carried with the actual return earned by the bank. Determination of the ratio between BNI Syariah results with user customer funds made by setting the level of expected return and the bank’s expected return rate of user client funds. Bank’s expected return level is calculated based customer’s of fund provider’s expected return estimation, the estimated overhead cost, estimation of risk level, and the expected net profit of the bank. While the level of expected return customers entrepreneur is the difference between the projected benefit the customer’s business and the expected return rate of the bank.Keywords: Profit Sharing Ratio, Mudaraba Agreement, Musharaka Agreement, Expected Return, Islamic Banking.